KETIKA TERMOHON MENOLAK TERLIBAT DALAM PERSIDANGAN ARBITRASE - Wiko, Garuda (TANJUNGPURA LAW JOURNAL, 2019)
Although arbitration has been made based on the agreement of the parties and stated in writing in the Main Contract, this does not guarantee that the parties will immediately be willing to participate in the arbitration process when a dispute occurs. It is possible that one of the arbitration parties was absent and was not willing to be involved in the trial process. In very rare circumstances, the arbitration applicant may cancel / deny his participation in the trial process. This article will describe the regulations, practices and expert views in the implementation of the arbitration proceedings without the presence of the respondent. It is expected that from this research, an overview will be obtained in carrying out the arbitration proceedings without the applicant. The findings obtained are that there are no extensive guidelines in Indonesia that can be used as a guide by the arbitrators in carrying out such a trial process, especially related to proof and examination of cases. Some of the principles and regulations set out in the Civil Procedure Code may be adopted to answer some things that are not regulated in the arbitration legal framework in Indonesia. Efforts should be made to develop a guideline framework for arbitrators so that there are similarities and quality assurance of decisions made in the trial process without the presence of the respondent.Meskipun arbitrase telah dibuat berdasarkan kesepakatan para pihak dan dicantumkan secara tertulis di dalam Kontrak Utamanya, hal ini tidak menjamin bahwa para pihak akan serta merta bersedia untuk berpartisipasi dalam proses arbitrase ketika suatu sengketa terjadi. Ada kemungkinan salah satu pihak arbitrase mangkir dan tidak bersedia terlibat dalam proses persidangan. Dalam kondisi yang sangat jarang, termohon arbitrase dapat membatalkan/mengingkari keikutsertaannya dalam proses persidangan. Artikel ini akan mendeskripsikan regulasi, praktik dan pandangan ahli dalam pelaksanaan proses persidangan arbitrase yang dilakukan tanpa kehadiran termohon. Diharapkan dari penulisan ini didapatkan gambaran terkait proses persidangan arbitrase tanpa pihak termohon. Penemuan yang didapat adalah belum ada pedoman yang ekstensif di Indonesia yang dapat dijadikan pedoman oleh arbiter dalam menjalankan proses persidangan seperti itu terutama terkait dengan pembuktian dan pemeriksaan perkara. Beberapa prinsip dan peraturan yang diatur dalam Hukum Acara Perdata mungkin dapat diadopsi untuk menjawab beberapa hal yang tidak diatur di dalam kerangka hukum arbitrase di Indonesia. Perlu adanya upaya untuk mengembangkan suatu kerangka pedoman bagi para arbiter agar terdapat kesamaan dan penjaminan kualitas terhadap putusan-putusan yang dibuat dalam proses persidangan tanpa kehadiran termohon.